ANALYSIS ON FACTORS THAT AFFECT STOCK PRICE: A STUDY ON PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION COMPANIES AT INDONESIA STOCK EXCHANGE - Chandra, Cindy Novita; Osesoga, Maria Stefani (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract” This study expects to determine the impact of Earnings Per Share (EPS), Current Ratio, Return On Asset (ROA), and Debt to Equity Ratio (DER) towards stock price of property and real estate firms. The samples consist of 37 property, real estate and building construction companies that were listed in Indonesia Stock Exchange period 2017–2019. Samples criteria were: listed on Indonesian Stock Exchange during 2017–2019; did not suspend by Indonesian Stock Exchange; published financial statements during 2017 – 2019; had closing date on December 31th, using Rupiah as reporting currency and published audited financial statement; have positive income; and did not do share splits and stock reverse during 2017 – 2019. The data was analysed by using multiple regression method. The result of this study are: EPS has positive significant impact to stock price, Current Ratio has no positive impact to stock price, while ROA and DER have negative significant impact to stock price. All the independent variables had significant impact on stock price simultaneously. Keywords: Current Ratio; DER; EPS; ROA; Stock Price